Kajian Pelaksanaan Program Bantuan Langsung Tunai Pada Rumah Tangga Miskin (Studi Kasus di Wilayah Kecamatan Sumbang Kabupaten Banyumas) - Suharno Suharno; Endang Setiasih (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2006)
The objective of the research are to describe; the mechanism of Direct Cash Helping (Bantuan Langsung Tunai/BLT) program in Sumbang district be a tool to solve the society poorness, the BLT program realization, the factors of supported and resisted of BLT program, to find out better solution which is through of BLT program in Sumbang district, and to analyze whether the BLT program can be overcome the society poorness in Sumbang district. Population of the research are 9,934 impecunious domestic in Sumbang district, so the number of minimum samples which must be taken at mistake storey level 0,1 % is equal to 100 respondents. Sample collection is done randomly in 19 countryside of Sumbang district. This Research is direct with the mixing method approach which use between qualitative and quantitative research. To analyze whether there is consideration difference to use of the BLT program, before and after direct aid execution, is used Cochran'S statistisk non-parametrik analysis with the SPSS program at the significant storey at 90% (a =10%) level. From the result analyses, there is no difference between respondents who had received the aid, before and after execution of acceptance BLT, that is for the accomplishment of daily meal requirement and their debt payment. Keywords : BLT program, poorness